A review on LiFi network research: open issues, applications and future directions - Badeel, Rozin; Subramaniam, Shamala; Mohd Hanapi, Zurina; Muhammed, Abdullah (Multidisciplinary Digital Publishing Institute, 2021)
This paper extensively reviews and analyses Light Fidelity (LiFi), a new technology that uses light to transmit data as a high-speed wireless connection system from a wide spectrum of domains. An in-depth analysis and classifications of pertinent research areas for LiFi networks are presented in this paper. The various aspects constituting this paper include a detailed literature review, proposed classifications, and statistics, which further is deliberated to encompass applications, system architecture, system components, advantages, and disadvantages. LiFi and other technologies are compared, multi-user access techniques used in LiFi networks are investigated and open issues are addressed in detail. The paper is concluded with a comprehensive taxonomy of literature comparison that has served as the basis of the proposed open issues and research trends.